Interactions Between Amino Acid Transport Systems in Neurospora crassa - Sanchez, S. (1972)
Mutants of Neurospora crassa, selected as resistant to l-canavanine and l-thialysine, are partially deficient in the uptake of basic amino acids. Neutral amino acids completely inhibit uptake of basic amino acids, and this inhibition is dependent on the activity of a neutral amino acid permease. In contradistinction, mutants resistant to 4-methyl-dl-tryptophan are partially deficient in the uptake of neutral amino acids. Basic amino acids completely inhibit neutral amino acid uptake, and this inhibition is dependent on the activity of a basic amino acid permease. It is proposed that these specific transport systems compete with a general amino acid permease for some common element. The general permease is also regulated by ammonia, the amino acid pool, or both. The activity of the general permease can be eliminated phenotypically by a high concentration of glycerol or a high temperature. It is also shown that l-citrulline is transported by the neutral amino acid permease and by the general amino acid permease.